2019
DOI: 10.3354/meps12924
|View full text |Cite
|
Sign up to set email alerts
|

The collapse and continued low productivity of a keystone forage fish species

Abstract: Capelin are a focal forage species in the Northwest Atlantic ecosystem as they act as an energy conduit from lower to higher trophic levels. Fisheries and Oceans Canada determined that the Newfoundland capelin stock (Northwest Atlantic Fisheries Organization Divisions 2J3KL) suffered an order of magnitude decline in biomass in 1990−1991. This collapse was concomitant with drastic changes observed in the ecosystem during the late 1980s and early 1990s. While the results of more than a dozen studies have support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 64 publications
1
32
0
Order By: Relevance
“…In contrast, Carscadden and Frank () found no correlation between capelin body condition and temperature in Newfoundland; however, they did find high capelin condition during the 1980s followed by a decade of low condition in the 1990s. Later studies revealed that this decadal‐scale change in condition coincided with a regime shift in which capelin and cod ( Gadus morhua ) populations both crashed after 1990 and remained extremely low until after the mid‐2000s (Buren et al, , ; Rose & Rowe, ). In this region, zooplankton stocks also crashed during the 1990s, so the food supply for capelin may have been limited (Carscadden & Frank, ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Carscadden and Frank () found no correlation between capelin body condition and temperature in Newfoundland; however, they did find high capelin condition during the 1980s followed by a decade of low condition in the 1990s. Later studies revealed that this decadal‐scale change in condition coincided with a regime shift in which capelin and cod ( Gadus morhua ) populations both crashed after 1990 and remained extremely low until after the mid‐2000s (Buren et al, , ; Rose & Rowe, ). In this region, zooplankton stocks also crashed during the 1990s, so the food supply for capelin may have been limited (Carscadden & Frank, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the collapse of the Atlantic cod stocks on the Newfoundland and Labrador shelves was the most visible change among groundfish, it was part of a synchronous decline in the biomass of a number of other commercial and non-targeted fish species, and a shift to an ecosystem dominated by shellfish such as northern shrimp (Pandalus borealis) and snow crab (Chionoecetes opilio). During the early 1990s, there was also an order of magnitude decline in biomass of capelin, the key forage fish in these ecosystems (Buren et al, 2014(Buren et al, , 2019. These dramatic changes, recognized as a regime shift, caused a reorganization of the fish community, as well as loss of its spatial structure and functional diversity (Buren et al, 2014(Buren et al, , 2019Dempsey et al, 2017;Pedersen et al, 2017Pedersen et al, , 2020.…”
Section: Changes In Prey Assemblagesmentioning
confidence: 99%
“…During the early 1990s, there was also an order of magnitude decline in biomass of capelin, the key forage fish in these ecosystems (Buren et al, 2014(Buren et al, , 2019. These dramatic changes, recognized as a regime shift, caused a reorganization of the fish community, as well as loss of its spatial structure and functional diversity (Buren et al, 2014(Buren et al, , 2019Dempsey et al, 2017;Pedersen et al, 2017Pedersen et al, , 2020. Following the cold period in the late 1980s and early 1990s, the water has warmed.…”
Section: Changes In Prey Assemblagesmentioning
confidence: 99%
“…The capelin stock on the Newfoundland and Labrador (Canada) continental shelf (North Atlantic Fisheries Organization [NAFO] Div. 2J3KL capelin stock; hereafter the Newfoundland capelin stock) has decreased dramatically from a high of 6 million tonnes (Mt) in the late 1980s to 0.02−0.06 Mt in 1990−1991 with minimal recovery over the past 28 yr (DFO 2018, Buren et al 2019). The decline in capelin biomass coincided with a regime shift in the NW Atlantic ecosystem during the late 1980s and early 1990s (DeYoung & Rose 1993, Pedersen et al 2017.…”
Section: Introductionmentioning
confidence: 99%